ENHANCING ISLAMIC-BASED LANGUAGE LITERACY: THE ROLES AND PERCEPTIONS OF INDONESIAN PRIMARY SCHOOL TEACHERS - Taranindya Zulhi Amalia; Sri Wuli Fitiati; Januarius Mujiyanto; Utami Widiati (English Review: Journal of English Education, 2025)
Increasing public awareness of improving Islamic-based language literacy in primary schools is the background to this study. It discusses a new perspective: improving literacy that incorporates Islamic values. It explores the roles of primary school English teachers in Islamic schools in Central Java, Indonesia, and their perceptions regarding improving students' Islamic-based language literacy. Using qualitative methods through purposive sampling, five teachers from five Islamic primary schools were selected to represent a population of 137 schools. Data were collected through surveys and documentation. The results showed that English teachers have served as cultural mediators and value integrators in improving students’ literacy. It closely relates to their teaching strategies. These highlight the importance of professional development and innovative teaching strategies integrating language, culture, and spirituality. Teachers also believed that the most effective way to incorporate Islamic language literacy into Islamic schools was through a multimedia approach that connected with local culture, making it culturally relevant while embedding religious values into the learning process. This study faced the challenge of a lack of previous research demonstrating the success of incorporating Islamic principles into English teaching. For this reason, the study was considered innovative for combining Islamic values with English learning.